HIFEMA TRAUMATIKA : LAPORAN KASUS - Aprilia Elisabet; Junita Shara (Pusat riset dan Inovasi Nasional, 2022)
Oculi trauma is one of the emergency cases in ophthalmology that happens often and usually can cause permanent vision loss. Traumatic hyphema is caused by blunt or penetrating injury and can accumulate blood mixed with aqueous humor in camera oculi anterior. Case report a 51-year-old male patient came to the hospital complaining of visual loss in his left eye after being hit by a rock. There was increasing intraocular pressure with blood in the camera oculi anterior, which may cause vision to decrease. The basic principles of the treatment in this patient are giving prophylaxis, decreasing intraocular pressure, and follow-up relating to the medication because complications such as secondary bleeding and infection may happen.